2006
DOI: 10.1164/rccm.200505-820oc
|View full text |Cite
|
Sign up to set email alerts
|

Oral Decontamination with Chlorhexidine Reduces the Incidence of Ventilator-associated Pneumonia

Abstract: Topical oral decontamination with CHX or CHX/COL reduces the incidence of VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
261
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(289 citation statements)
references
References 57 publications
4
261
0
14
Order By: Relevance
“…Chlorhexidine at varying concentrations, however, has been evaluated in more than 11 trials. Impacts on VAP rates have been variable: three reported decreases [64][65][66] while the other eight did not [67][68][69][70][71][72][73][74]. One trial reported a decrease in antibiotic usage for patients treated with chlorhexidine [67].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorhexidine at varying concentrations, however, has been evaluated in more than 11 trials. Impacts on VAP rates have been variable: three reported decreases [64][65][66] while the other eight did not [67][68][69][70][71][72][73][74]. One trial reported a decrease in antibiotic usage for patients treated with chlorhexidine [67].…”
Section: Oral Antiseptics and Antibioticsmentioning
confidence: 99%
“…Subgroup ana lysis of chlorhexidine trials suggest that it has less activity against Gram-negatives compared with Gram-positives [70,74]. This may be due to a differential effect of the antiseptic or it may suggest an unaddressed reservoir of bacteria in the stomach and GI tract where Gram-negatives predominate.…”
Section: Reviewmentioning
confidence: 99%
“…(Masterton et al, 2008) Many participants seemed to confuse the oral component of SDD with routine mouthcare using chlorhexidine. The reference was not to selective oral decontamination (SOD), which is the administration of oral antimicrobials and omitting the intestinal and parenteral components, important to differentiate chlorhexidine as an antiseptic (Koeman et al, 2006, Labeau et al, 2011) from the use of topical, non-absorbable antibiotics that feature as a component of SDD. The primary concern for delivering SDD to critically ill patients was the potential for development of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Decontamination with antibiotics reduces the incidence of VAP [11], but it is not currently recommended because of concern for possible selection of resistant bacteria. Oropharyngeal rinse with chlorhexidine was shown to be eff ective in reducing tracheal colonization and VAP incidence in a randomized, placebo-controlled study on nearly 400 patients [12], and is now widely used as standard of care for the intubated patient.…”
Section: Oral Carementioning
confidence: 99%